Breast cancer neoadjuvant endocrine therapy and COVID-19: a renewed breath with future perspectives - Gouveia, Maria Carolina; Andrade, Raffaela Levy de; Marques, Larissa Cabral; Santos, Candice Amorim de Araujo Lima; Souza, Ariani Impieri (Mastology, 2020)
In 2020, the COVID-19 pandemic is the major healthcare concern around the world. The infection is especially severe to those with immune system suppression, including patients with cancer. In order to mitigate the negative effects of COVID-19, guidelines have been developed by societies worldwide to review oncology care during this pandemic time. Neoadjuvant endocrine therapy (NET) is a well-stablished option for hormone positive (HR) HER2 negative breast cancer and showed a positive response in breast conservative surgery with substantially less toxicity. Compared to chemotherapy, the NET cost is lower, and its administration is easier, due to less medical visits. Even with remarkable advantages, NET remains taking less place in treatments than it might have. Periods of humanity crisis, such as World Wars and other pandemics, boosted the development of science and established many treatments, which are currently practiced. New data generated during the COVID-19 outbreak can inspire more trials comparing chemotherapy to endocrine therapy within the neoadjuvant setting. The purpose of this letter is to suggest NET as a safe low toxicity treatment strategy for breast cancer, not only to postpone breast cancer surgery during the pandemic, but also to become a standard therapy, a flame kept burning crossing the COVID-19 border.